Hollow Bulb Obturator for Rehabilitation of Maxillary Resection - Upreti, S; Thakur, SN; Mishra, S; Rajbanshi, MK (Journal of Nepalese Prosthodontic Society, 2024)
Maxillary resection of tumors can result in significant functional and aesthetic challenges for patients. This case report describes successful rehabilitation of a patient who underwent partial maxillary resection following tumor removal. A custom-made hollow-bulb obturator was used to restore the oral function and facial aesthetics. This report outlines the treatment process, prosthetic design, clinical and prosthetic aspects of the interim obturator, prosthesis fabrication and patient adaptation.